Changes in pulmonary function and patient-reported outcomes during COVID-19 recovery: a longitudinal, prospective cohort study. Issue 3 (13th September 2021) - Shah, Aditi S.; Ryu, Min Hyung; Hague, Cameron J.; Murphy, Darra T.; Johnston, James C.; Ryerson, Christopher J.; Carlsten, Christopher; Wong, Alyson W.
Objectives: The aim of this study was to compare respiratory and patient-reported outcome measures (PROMs) between 3 and 6 months after symptom onset and to identify features that predict these changes. Methods: This was a consecutive prospective cohort of 73 patients who were hospitalised with coronavirus disease 2019 (COVID-19). We evaluated the changes in pulmonary function tests and PROMs between 3 and 6 months and then investigated the associations between outcomes (change in diffusing capacity of the lung for carbon monoxide ( D LCO ), dyspnoea and quality of life (QoL)) and clinical and radiological features. Results: There was improvement in forced vital capacity, total lung capacity and D LCO between 3 and 6 months by 3.25%, 3.82% and 5.69%, respectively; however, there was no difference in PROMs. Reticulation and total computed tomography (CT) scores were associated with lower D LCO % predicted at 6 months (coefficients; −8.7 and −5.3, respectively). The association between radiological scores and D LCO were modified by time, with the degree of association between ground glass and D LCO having decreased markedly over time. There was no association between other predictors and change in dyspnoea or QoL over time. Conclusions: There is improvement in pulmonary function measurements between 3 and 6 months after COVID-19 symptom onset; however, PROMs did not improve. A higher reticulation and total CT score are negatively associated with D LCO, but this association is attenuated over time. Lastly, there is a considerable proportion of patients with unexplained dyspnoea at 6 months, motivating further research to identify the underlying mechanisms. #COVID19 survivors have improvement in pulmonary function at 6 months. However, 83% have abnormal patient-reported outcomes with 42% reporting persistent dyspnoea despite some with normal D LCO . Imaging features at 3 months can help predict D LCO trajectory. https://bit.ly/3gEErST